Firm-level pay agreements and within-firm wage inequalities: Evidence across Europe - Valeria Cirillo; Matteo Sostero; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
This article investigates the relation linking single-employer bargaining and within-firm wage dispersion - a significant driver of overall wage inequality. The study considers six European economies (Belgium, Spain, Germany, France, the Czech Republic and the UK), featuring different collective bargaining institutions, in 2006 and 2010. We examine two different measures of within-firm inequality, allowing to capture how different groups of employees (top vs. bottom paid, and managers vs. low-layer employees) may differently benefit or lose from firm-level bargaining. Our findings show that firm-level bargaining has heterogeneous effects across countries, over time and by inequality measures. We interpret our evidence as supporting that country-specificities and the heterogeneous balance of power within organizations represent key elements to understand the role of the bargaining system in shaping inequalities.
Keywords: J31; J33; J51; J52; 330; within-firm wage inequalities; occupational wage-gap; firm-level bargaining; matched employer-employee data